Laboratory optimization of the production of guanidium-based inactivated transport media to support SARS-CoV-2 PCR testing in Indonesia - Shabarni Gaffar,, Hesti Lina Wiraswati,,, Savira Ekawardhani,,, Lia Faridah,,, Nisa Fauziah,,, Amila Laelalugina, Annisa Retno Arimdayu, Chanda Taruna Adiarka Utomo, Maulana Ihsan, Ikhwan Ramadhana, Sanny Hafidhoh Siti Nururrohmah, Trifanny Nur Azizah, Mia Tria Novianti,, Radewi Safira Fauzia (Journal of Applied Pharmaceutical Science, 2022)
The availability of a viral transport medium (VTM) is often an obstacle to COVID-19 testing, especially for countries that are not VTM producers, including Indonesia. Therefore, the Parasitology Laboratory of Medicinal Faculty, Universitas Padjadjaran, Indonesia, developed an inactivation transport medium called “VITPAD®” that uses a guanidium-based buffer solution. This study evaluated VITPAD® as a transport medium for swab samples and scaled-up production from 2,000 tubes per month to 60,000 per month to support COVID-19 testing in Indonesia. VITPAD® has good stability and sterility, with a lifespan of over 2 years, and it performs well as a transport medium for COVID-19 samples. The production capacity was successfully scaled-up by implementing scheduling and capacity management, with the first large-scale production of VITPAD® distributed to 26 teaching hospitals in Indonesia.
Keywords: Guanidium-based buffer, inactivation transport media, polymerase chain reaction, production capacity